ANALYSIS OF CONSTRUCTION OF STRUCTURE OF STUDY MATERIAL FOR GROUP WORK ON TECHNICAL PROFILE (Pedagogy of Higher and Secondary Education, 2022)
The analysis of the construction of the structure of educational material is conducted for work of the group on a technical type on the basis of the principle of ascent from abstract to concrete, that allowed to inculcate technology of developing studies in school practice. Certainly such construction of structure of educational materiaí most effective for work of the group on a technical type.
Keywords: principle of ascent from ahstract to concrete; consruction of structure of educational material; anaysis and synthesis of concepts of course of inorganic chemistry